1997
DOI: 10.1590/s0034-89101997000300007
|View full text |Cite
|
Sign up to set email alerts
|

Análise de concordância entre informações referidas e observadas acerca do estadiamento pubertário entre escolares do sexo feminino

Abstract: Significant events, such as the beginning of pubertal development, the menarche and the showing down of the body's development growth could be determined with acceptable levels of agreement. The low agreement rates observed for the simultaneous analysis of the degree of both breast and public hair show the need for the perfecting of methodologies that can replace the physical examination of adolescents, once reliable information about pubertal development is obtained in field studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…There is evidence that concordance increases when real photographs in color are used, when supporting texts with a short description of each image are used and adapted to local language [16], or if the girl has the opportunity to look at herself in a full-length mirror during the self-assessment [6]. Finally, another possible reason for the low agreement of the self-assessment is the young ages of our children which ranged from 6–9 years old [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that concordance increases when real photographs in color are used, when supporting texts with a short description of each image are used and adapted to local language [16], or if the girl has the opportunity to look at herself in a full-length mirror during the self-assessment [6]. Finally, another possible reason for the low agreement of the self-assessment is the young ages of our children which ranged from 6–9 years old [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors have indicated that the selfobservation techniques of pubertal development following Tanner's standardization may be liable to errors. 36 Owing to the existence of ethnic differences that compromise the definition of the adolescents' sexual maturation stage, 37,38 other studies have recommended caution on the classification of pubertal development.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, Guimarães & Passos 24 analisaram a concordância entre informações referidas e observadas do EMS de meninas. Os percentuais de concordância para desenvolvimento das mamas variaram de 57,3 a 65,2% e, para os pelos pubianos, entre 65,4 e 73,5%, valores inferiores aos apresentados na literatura, segundo os autores.…”
Section: Obesidade Maternaunclassified